The social portrait of child with disability as conceived by population of the Euro-Arctic region of Russia - Zhigunova, G V (Problemy sotsial'noi gigieny, zdravookhraneniia i istorii meditsiny, 2023)
The problem of perceiving person with disability as "atypical" individual is one of the most acute in modern society. The stereotypes and fears existing in conceptions of citizens regarding this category are negatively reflected in current intensive inclusive processes. The most negatively negative conceptions about persons with disabilities affect children population, aggravating processes of socialization and inclusion in social practices inherent to their "norm-typical" peers. The survey of population of the Euro-Arctic region, carried out by the author in 2022, to identify characteristics of perception of children with disabilities, established that negative perceptions prevail in assessments of children with disabilities. The results demonstrated that, basically, disabled subjects are perceived through assessments of their personal and behavioral characteristics, and not through the social conditions of their life. The results of the study made it possible to conclude that medical model of disability significantly impact on citizens' perceptions of persons with disabilities. The phenomenon of disability itself can be attributed to factors contributing to negative labeling of its subjects. The conclusions and results of the study can be used to develop positive image of disabled perdsons in the Russian socium in process of further development of inclusive processes.